FIGURATIVE CHEKHOVIANA IN THE DON AND SEA OF AZOV REGION: THE SYMBOLISM OF DETAILS (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-1-24-36The figurative (fine arts) Chekhoviana of the Don and the Sea of Azov Region addresses the symbolism of details, as well as Anton Pavlovich Chekhov did in his works, which allow the readers ‘deciphering’ the author’s ideas. The art is symbolic in itself, by its nature. However, the symbols in Chekhov’s oeuvre have nothing mystical and rather are linked to the everyday life. The works in various techniques by the artists of Southern Russia considered in the study are not the illustrations of the Chekhov’s works but the reflections on the literary Chekhovian text. The artists, applying the means of fine arts, emphasize the symbolic nature of the images of garden, road and crossroad, dog, etc.Key words: Anton Pavlovich Chekhov, fine arts, symbol, Southern RussiaAcknowledgments: The authors are grateful to painters M.P. Volodina and A.A. Kostina, art historian G.A. Korobova, director of the State literary-memorial museum-reservation of A.P. Chekhov “Melikhovo” A.A. Zhuravlyova, the main guardian of Taganrog Art Museum O.V. Kostina, junior researcher of East-Crimean historical-cultural museum-reserve A. Yu. Kuznetsova and researcher of that museum A.I. Naumenko for information support and Ya. Yu. Yakovleva for the computer processing of pictures.The publication was prepared as part of the implementation of the SO of the Southern Scientific Center of the Russian Academy of Sciences "Political and socio-cultural processes in the South of Russia in the context of modernization (XVII – XXI centuries)", project no. 122020100347-2.